The KARAKTERISTIK FISIK PATI GEMBILI (Dioscorea esculenta L.) DAN TALAS (Colocasia esculenta L.) TERMODIFIKASI ALKOHOL-BASA - Parwiyanti, Parwiyanti Parwiyanti; Mahayati, Nura; Lidiasari, Eka; Nurjannah, Tri (Program Studi Magister Ilmu Pertanian, Fakultas Pertanian, Fakultas Pertanian, Perikanan dan Biologi Universitas Bangka Belitung, 2024)
Modification of Dioscorea esculenta and Colocasia esculenta starch through NaOH-Etanol was conducted to improve and expand the use of this starch in instant product, especially as binding agent of laksa instant. This study aimed to determine the effect of varying amounts of NaOH on physical characteristics of lesser yam and taro starch. The research was conducted at Agricultural Product Chemical Laboratory, Agricultural Technology Department, Faculty of Agriculture, Sriwijaya University. This study used a Split Plot Design with two treatment factors were the types of starch (lesser yam and taro) and varying amounts of NaOH 3 M (0, 3, 6, 9 g). The parameters observed included whiteness level, water solubility, water absorption index, solubility index, and swelling power. The results showed that the type of starch had significantly affected on water absorption index, water solubility, swelling power, solubility index of modified starch. The amount of NaOH had significantly affected on whiteness level, water absorption index. water solubility, swelling power, solubility inde of modified starch. Moreover, the interaction between types of starch and the amount of NaOH had significantly affected on water absorption index, solubility in water, solubility index of modified starch. The best treatment was lesser yam starch with the addition 3 g of NaOH 3M as binding agent.